The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.7326/0003-4819-110-2-151
|View full text |Cite
|
Sign up to set email alerts
|

Health Science Information Management and Continuing Education of Physicians

Abstract: Primary practitioners require substantial help in meeting current science information needs. Increase in such resources as "validated reviews" or "expert networks" might help meet these needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(48 citation statements)
references
References 4 publications
2
45
0
1
Order By: Relevance
“…It has also been shown that, at least under some circumstances, information can be found using computer systems and a limited amount of resources [8,9]. According to Lindberg et al, literature retrieval systems such as MEDLINE may be used by health care providers to meet clinical information needs [10], but according to Williamson et al [3] many physicians (38%) nd the eå ort necessary to get information from the literature to be a major problem. Other problems mentioned are nding time to look for information and sorting out irrelevant material.…”
Section: Information Needs Sources and Usefulnessmentioning
confidence: 98%
See 1 more Smart Citation
“…It has also been shown that, at least under some circumstances, information can be found using computer systems and a limited amount of resources [8,9]. According to Lindberg et al, literature retrieval systems such as MEDLINE may be used by health care providers to meet clinical information needs [10], but according to Williamson et al [3] many physicians (38%) nd the eå ort necessary to get information from the literature to be a major problem. Other problems mentioned are nding time to look for information and sorting out irrelevant material.…”
Section: Information Needs Sources and Usefulnessmentioning
confidence: 98%
“…Health care providers are faced with a major problem in keeping up to date with developments in clinical medicine [3]. Reduced funding in the health care organizations of today increases the demand for decentralized and cost-eå ective decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…22 A correlation matrix of all studied variables was performed to recognize previous relationships among the metals concentration and cluster analysis was used to identify and study the interrelationships among variables (metals) and sites with similar behaviors. These statistical analyses were carried out using SSPSS 11.0 software package for Windows.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Survey methodology is popular in studying large medical populations (Stinson & Muller, 1980;Strasser, 1978;Williamson, German, Weiss, Skinner, & Bowes, 1989). For example, Stinson and Muller interviewed 400 randomly selected Alabama health professionals in an effort to identify "the information habits health professionals used to stay abreast of current advances in medicine.…”
Section: Methods Used To Study Information Seeking Behaviormentioning
confidence: 99%